High resolution structural evidence suggests the Sarcoplasmic Reticulum forms microdomains with Acidic Stores (lysosomes) in the heart. - Aston, D; Capel, R; Ford, K; Christian, H; Mirams, G; Rog-Zielinska, E; Kohl, P; Galione, A; Burton, R; Terrar, D (Nature Publishing Group, 2017)
Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) stimulates calcium release from acidic stores such as lysosomes and is a highly potent calcium-mobilising second messenger. NAADP plays an important role in calcium signalling in the heart under basal conditions and following β-adrenergic stress. Nevertheless, the spatial interaction of acidic stores with other parts of the calcium signalling apparatus in cardiac myocytes is unknown. We present evidence that lysosomes are intimately associated with the sarcoplasmic reticulum (SR) in ventricular myocytes; a median separation of 20 nm in 2D electron microscopy and 3.3 nm in 3D electron tomography indicates a genuine signalling microdomain between these organelles. Fourier analysis of immunolabelled lysosomes suggests a sarcomeric pattern (dominant wavelength 1.80 μm). Furthermore, we show that lysosomes form close associations with mitochondria (median separation 6.2 nm in 3D studies) which may provide a basis for the recently-discovered role of NAADP in reperfusion-induced cell death. The trigger hypothesis for NAADP action proposes that calcium release from acidic stores subsequently acts to enhance calcium release from the SR. This work provides structural evidence in cardiac myocytes to indicate the formation of microdomains between acidic and SR calcium stores, supporting emerging interpretations of NAADP physiology and pharmacology in heart.